Функции цивилизационного сознания - Ионов, И. (Інститут історії України НАН України, 2008)
Сivilizational analisys’ method is not only plate scienticism and objectivistic positivism. Here different precognitive and later cognitive functions of civilizational analisys are represented, mainly the three. The first of the precognitive function is self -identification, and the use of the negative valuated Other, “the Abject”. This is the base of imperialistic “Orientalism” and the principle of cultural recolonisation of World Periphery. The second is the communic ative one, based on objectivist monologic or subject-subject dialogocal way of knowledge (M.M.Bachtin’s). The third describes the transition of primitive mental maps to modern (and post -modern) cognitive maps. The main is the way from apodictical objectivi stic macro schemata forming one’s identity to the critical cognitive partial, convergentive dialogical models.